PENGARUH LAJU ALIR DAN TEMPERATUR UMPAN TERHADAP KADAR AIR MINYAK KELUARAN OIL PURIFIER UNIT KLARIFIKASI: STUDI PADA PALM OIL MILL - Sari, Thania Yosrima; Youfa, Rita (Politeknik ATI Padang, 2020)
Crude Palm Oil (CPO) is a vegetable oil extracted from the mesocarp or flesh of the oil palm fruit after several processes of oil and kernel separation. One of the key steps in CPO processing is the oil purification stage at the clarification station, where an essential piece of equipment used is the Oil Purifier. During this stage, the purification process is crucial because if the oil still contains impurities or a high amount of water, it can degrade the quality of the oil. Therefore, the Oil Purifier must be carefully managed in the CPO processing because this process involves separating oil, water, and impurities before the oil is pumped to the vacuum dryer. If the purifier does not function properly, it can negatively affect the quality of the oil produced. Hence, a reassessment of the Oil Purifier in the Clarification Unit is necessary. The procedure for analyzing the samples involves assessing the moisture and impurity content in AOP (After Oil Purifier) and BOP (Before Oil Purifier) samples. The results indicate that the feed temperature significantly affects the moisture content in the Oil Purifier's output. Additionally, the feed flow rate also has a substantial impact on the moisture content in the Oil Purifier's output, where the moisture content of the oil from the purifier is related to the moisture content of the feed oil entering the purifier.